Penguatan Digitalisasi Pemasaran dalam Meningkatkan Kinerja UMKM di Kota Cilegon dan Serang - Saeful Fachri; Muhammad Fauzi; Willy Nurhayadi; Urfanul Aulia (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
Marketing digitalization is something that cannot be avoided by MSMEs to improve their business performance. The obstacles faced by MSME players in the supporting cities of Banten Province, namely Serang and Cilegon, where they still have not utilized access to digital media in their business activities, namely because they still have business ideas that are carried out only to meet the needs of the local community or around them, they still do not master marketing methods with digital media. Such as.Whatsapp, Instagram, Facebook, or other marketplaces. The aim of implementing PKM is that it is hoped that MSME actors can apply various training materials and continue and develop marketing through digital media, including digital market platforms, namely those developed by the government and the private sector.